PARTICULARITIES OF THE HUMAN RESOURCE MOTIVATION IN PUBLIC ADMINISTRATION - IOAN CONSTANTIN DIMA; VERGIL CIUREA; IOAN VOICU; MIHAELA SANDU (Annals of the University of Petrosani: Economics)
The notion of public administration bears several acceptations, an activity one, of functional meaning and an organisational one. In both ways, public administration is indissolubly connected to the state. In default of the state, there is no public administration, as this is a state activity, performed by government bodies. This affirmation is confirmed by the stipulations of the Romanian Constitution, called public Authorities, chapter V, titled Public Administration. The first section intended for the specialised central public administration (ministry, other central bodies), and a second section is dedicated to the local public administration (county councils, local councils, mayors). There is no doubt that both sections refer to government bodies performing a state activity, so that the central specialised bodies of the public administration as well as the local bodies of the public administration are government bodies, and the activity they perform is a state one.